(3QSGdI aj GdaQb Hjf GdMQGQI GdZQjRjI hGdMQGQI GdZQjHIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje , JQi CUfGa GdMjhGf hGdfHGJ JJe CaYGdgG GdZPGFjI hGdJhdjOjI HMQGQI eMShSI s
(3BNQgG (B:s
(3hEf cGf EUGHI GdMb KeI HeKd gPG GdfXQ , hefg jgJOi Edjg , hGdMeO ddg QH GdYGdejf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B108 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs